Decision Support System Decision Support System (DSS) For Determining Scholarships Using The MOORA Method - M Yogi; Saputra, Eki; Fronita, Mona; Muhammad Lutfi Hamzah (Jurnal Sistem Cerdas, 2024)
A decision support system is a system that uses computer technology to assist decision making. Every year, Baznas Riau Province conducts a selection process for scholarship acceptance. Scholarships are financial assistance for individuals, both students and students, for educational purposes. In the scholarship selection process, there are several criteria and sub-criteria, including KTP, educational status (not yet a graduate), GPA, parents' income, and housing conditions. The existence of quotas and specific criteria that must be met makes it difficult for Baznas Riau Province to select prospective scholarship recipients. This research implements the MOORA method, which was chosen for its simplicity, effectiveness, stability, and ability to produce accurate judgments in decision-making when compared to other methods. This method is simple and practical to use, and optimizes various objectives based on ratio analysis by giving values or weights to each predetermined criterion. After testing using the MOORA method, results were obtained from 13 students tested, where the highest value was obtained by A12 (Maya Sari) with a value of 0.2454 and the lowest value by A11 (Rizka Syaputri) with a value of 0.1987. The final result of this research produces a decision support system to determine scholarship recipients at Baznas Riau Province, which is expected to help Baznas in the scholarship selection process and increase efficiency in its implementation.